Diseño y construcción de filtro funcional para filtrar las impurezas del agua cruda, con énfasis en los análisis físico-químicos para la calidad del agua (2023)
This project is focused on the design and construction of a filter for the gray water coming out of the washing machine,this scale prototype was designed with the help of a calculation memory where the output flow, the infiltration rate are specified. , volume, area, diameter, thickness of the filtering beds, etc. The filter was built with materials that met the cost-benefit proposed in the project, functionality and durability tests were carried out on the prototype, which endorsed its proper functioning. Once the proper functioning was confirmed, the tests were carried out on the filtering beds with different combinations and thicknesses of the materials; To obtain the percentages of removals given by the different tests carried out on the beds, some initial physicochemical analysis were carried out and after this activity, they yield different removal results, giving the combination of beds (Anthracite-Zeolite-Activated Carbon) as the most efficient. with a 79.6% removal of total contaminants and giving COD and surfactants (SAAM) as the contaminants with the highest individual removal with each of the proposed bed combinations.